Prevalence of ovine fasciolosis and its economic significance in basona worana district, central Ethiopia - Zeleke, G.; Menkir, S.; Desta, M. (Scientific Journal of Zoology, 2013)
A cross-sectional andretrospective study was conducted from February-May, 2012 to determine theprevalence of ovine fasciolosis. A total of 1528 sheep were selected andsampled by using systematic simple random sampling, Sedimentation technique,haematocrite centrifugation and postmortem examination were employed during thestudy period. Overall prevalence of ovine fasciolosis based on farm, abattoirand retrospective clinical study was 62.7%, 52.6% and 59.1%, respectively.There was no statistically significant variations (p>0.05) by sex and age ofsheep in both farm and abattoir study. The association of ovine faciolosis withdifferent breeds of sheep was statistically significant variation (p<0.05)was observed in farm, abattoir and retrospective veterinary clinical dataanalysis. The prevalence of fasciolosis was different among FAMACHA eye-colourscores, body condition, mean PCV value, liver pathology, types of Fasciolaspecies and worm burden (p<0.05). The prevalence of ovine fasciolosis basedon FAMACHA eye-colour scores was highest (100%) in pink white and lowest in red(51.9%). The mean PCV value of Fasciola species in infected and uninfectedsheep were 24.04 ± .381 and 25.87 ± .516, respectively. The mean worm burden oflightly, moderately and severely affected livers was 21.00 ± 1.889, 34.30 ±2.662 and 105.09 ± 9.741, respectively. The average mean worm burden per affectedliver was 56.79 ± 4.635. The predominant species identified in the study areawas Fasciola hepatica (68.8%). The mean fluke burden of each Fasciola speciescounted was 47.17 ± 4.737, 25.50 ± 4.912 and 93.02 ± 12.139 for Fasciolahepatica, Fasciola gigantica and mixed Fasciola species infection,respectively. The prevalence of ovine fasciolosis in the study area should bereduced by sustainable and integrated control programmes which includestrategic application of anthelmintics, efficient farm and grazing managementby Veterinarians and sheep owners in the study area.